A randomised control trial comparing the efficacy of cord milking over the delayed cord clamping on serum ferritin level in preterm neonates at 6 weeks of age - Devadas, Sahana; R., Roshni; K., Mallesh (International Journal of Contemporary Pediatrics, 2020)
Background: Perinatal iron deficiency has received little attention in the past. Umbilical cord milking is a type of placental transfusion, they serve to potentially enhance neonatal blood volume and consequently the iron stores after birth. Among the neonates, the preterm infants are sick and vulnerable babies who are already deprived of iron stores. The aim of this study was to evaluate the effect of cord milking on ferritin values amongst preterm neonates. Methods: This is a hospital based randomized control trial which included the babies born at 29-36 weeks of gestation. The babies were randomized to two intervention groups; cord milking and delayed cord clamping group. Detailed clinical history taken, including details of labour and clinical examination. Blood samples were analysed for ferritin as required at 6 weeks of post-natal age. Results: Neonates under cord milking group had higher ferritin values (249.04±21.93 ng/mL) as compared to those neonates under delayed cord clamping group (179.66±32.94 ng/mL) and this was statistically very significant (p= <0.001). Conclusions: In preterm neonates, umbilical cord milking results in improved iron status as shown by higher ferritin values at 6 weeks of life. UCM can be a used as placental transfusion strategy in preterm neonates for improving iron status and preventing anemia of prematurity.